Population and Strategy Development in Buffaloes - Praharani, Lisa; Juarini, E; Thalib, Chalid; ., Ashari (Indonesian Animal Sciences Society, 2010)
Buffalo is a potential large ruminant that its contribution in national program on beef self sufficiency has been unrecognized in Indonesia. In rural community, buffalo has similar functions as cattle, it is used as draught animal, meat (beef) producer, saving, milk producer, sacrificial ritual animal to social status. The peak of buffalo population was on 1925, 3.227 million heads in Java and 1.10 million in outside Java. The centers of cattle production sites for national program of self sufficiency on beef were formly as noted the centers of buffalo production. The introduction of Bali cattle to those former buffalo centers particularly in outside of Java depressed buffalo population and then dominated by Bali cattle. Then Bali cattle were noted to be the major beef animal supplier beside buffalo to the centers of consumers for domestic and export. This article aims to discuss the depleting buffalo population and to formulate development strategy. Historical approaches system and critical evaluation population, SWOT (strength, weaknesses, opportunity and threat) analysis were used as tools for analyzing. Two case studies on herd survival from Banten indicated depleting population of buffalo. Despite low reproductive profile, strategic diseases and farmersâ institution needed to be optimized on services. Understanding criticizing on ecological habitats in the potential regions, the need of spatial planning for its development, zoning program for strategic diseases free, reproductive problems and village institution are the important areas of improvement for buffalo development in supporting beef self sufficiency and the welfare of rural people with their buffalo in sustainable beef production. Key words: Buffalo, population, sustainability, development strategy